On-site condition monitoring of PV modules assisted by aerial thermographic image analysis - -, -
The aim of this project is to analyze the most major problem in PV module, which is the solar hotspot. Many causes can lead to this kind of defects towards a PV module such as shading effect, impurities present on the module surface, and many more. In this research, the system will capture infrared images of the PV module using an infrared thermal camera and display the images on the LCD display. Region of module which having abnormal temperature can be detected. This region needed to be analysed in order to know if it is a hotspot or not. This system will analyze or check that particular region to automatically determine where is the hotspot had occurred.